Pengembangan Sistim LEISA untuk Meningkatkan Produktivitas dan Kualitas Umbi Kentang (Solanum Tuberosum L.) (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2017)
The research objective of applications LEISA (Low External Input on Sustainable Agriculture)system on the cultivation of potatoes was to increase productivity and quality of potatoes tubers.The experiment was designed with a randomized block design (CRD) with six treatments ofchicken manure compost fertilizer dosage. Dose fertilizing compost are: 0 ton/ha (as control), 10tons/ha, 12.5 tons/ha, 15 tons/ha, and 17.5 tons/ha and 20 tons/ha. This fertilizer was combinedwith NPK fertilizer 250 kg/ha. Parameters measured were: the physical properties of the soil, landfertility, the population of bacteria in the soil, land productivity and quality of potato tubers.LEISA systems with dose of compost 20 tons/ha are able to produce potatoes to 30.7 tons/ha or1.17 kg/tree. Total consumption of potato tuber from the research was 76.84 - 87.71%, while theclass of seed potatoes was 9.25 - 22.06%. Porosity of the soil was more than 50% with the abilityof soil to retain water 28 % w.b at doses of chicken manure fertilizer compost 15 tons/ha. At thisdose soil organic matter content of more than 5% with CEC was 23.8 me/100g or land wascategorized fertile soil. In addition, at pH close to neutral (6.8 to 6.9) existing bacterial populationwas 2.2 x 103 - 4.7 x 108 cfu.
Keywords: sistim LEISA; umbi kentang; kompos; produktivitas; kualitas